Assessment of Purity Parameters of Generic and Brand Name Losartan Potassium - Mattiazzi, Patricia; Bohrer, Denise; Viana, Carine; Becker, Emilene (Current Pharmaceutical Analysis, 2021)
Background: Generic products must be bioequivalent to the innovator brand product. Nevertheless, in addition to meeting bioequivalence standards, attention must be paid to the content of the active substance and contaminants in generic drugs. Objectives: This study compared the pharmaceutical quality of four generic losartan potassium formulations with the brand-name product: Cozaar®. Methods: The United States Pharmacopeia (USP) losartan potassium standard was used as reference material. The products tested (all 50 mg formulations) included four generic tablet formulations and the innovator brand product Cozaar®. Active substance content, organic impurities, and elemental impurities were assessed following the USP monograph for losartan potassium tablets and USP Chapter <233> on Elemental Impurities. Results: The results showed that three of the four generic products had low content of the active ingredient. The values ranged from 86.4 to 93.8%, being acceptable not below 95% of the labeled amount. Organic impurities were not detected in any of the products, and of the 13 elemental impurities tested, only four elements were detected. The elemental impurities Cr, Ni, Cu, and As were, however, in amounts within the limits established by the USP monograph. The only concern on the generic drugs analyzed was the low content of the active ingredient in 75% of the products. Conclusion: Since losartan is a drug of continuous use, lower content of the active ingredient may go unnoticed by the users of the generic product and entailed clinical consequences during long-term therapy.
Keywords: organic impurities